2017
DOI: 10.1016/j.jpor.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Masticatory function parameters in patients with varying degree of mandibular bone resorption

Abstract: Mandibular bone height does not directly affect the masticatory function and is inversely correlated with the self-perceived masticatory ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 22 publications
5
34
0
Order By: Relevance
“…Thus, the OHRQoL is impacted by a functional limitation caused by an unsatisfactory masticatory function of these individuals, which may be caused by irregular muscle activity or energy flow during mastication . This agrees with previous studies that pointed out that the lack of retention and instability found in complete dentures cause functional limitation, negatively impacting OHRQoL …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, the OHRQoL is impacted by a functional limitation caused by an unsatisfactory masticatory function of these individuals, which may be caused by irregular muscle activity or energy flow during mastication . This agrees with previous studies that pointed out that the lack of retention and instability found in complete dentures cause functional limitation, negatively impacting OHRQoL …”
Section: Discussionsupporting
confidence: 93%
“…Conventional complete dentures are still widely used to rehabilitate edentulous individuals in regions with economic limitations . However, a large number of complete denture wearers complain about the lack of retention and stability, especially in the mandible, which directly influences the masticatory function . Two implant‐retained mandibular overdentures provide a simple and cost‐effective alternative that should be implemented more frequently in low‐ and middle‐income countries .…”
mentioning
confidence: 99%
“…It should be pointed out that in Pan et al's study, of a total of 214 edentulous patients evaluated, 82.35% belonged to categories III and IV of the ACP PDI, where radiographic mandibular bone height is lower than 15 mm. Patient functional adaptation with CDs seems to be superior to the level of bone resorption for an improved masticatory performance …”
Section: Discussionmentioning
confidence: 99%
“…A single expert examiner (RMMM) performed the radiographic linear measurements to evaluate the mandibular bone height in the anterior and posterior region. The mandibular atrophy level was then determined following the methodology previously described by Marcello‐Machado et al …”
Section: Methodsmentioning
confidence: 99%